2009
DOI: 10.1136/bmj.b4817
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life three years after diagnosis of localised prostate cancer: population based cohort study

Abstract: Objective To quantify the risk and severity of negative effects of treatment for localised prostate cancer on long term quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
256
5
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(298 citation statements)
references
References 31 publications
(27 reference statements)
22
256
5
12
Order By: Relevance
“…Finally, adherence to treatment and acceptance of surgical risks may differ by SES. 21 Timely access to and provision of high quality cancer care is a key determinant for cancer outcomes. In our study, men with high SES, and in particular men with high income, had significantly shorter waiting times, more frequently received treatment with curative intent, and had better short-term surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, adherence to treatment and acceptance of surgical risks may differ by SES. 21 Timely access to and provision of high quality cancer care is a key determinant for cancer outcomes. In our study, men with high SES, and in particular men with high income, had significantly shorter waiting times, more frequently received treatment with curative intent, and had better short-term surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, there is a paucity of high quality evidence comparing these treatments to guide patients and clinicians in their treatment choices 5 and adverse effects including impotence are common, persistent and associated with reduced quality of life. 6,7 Men with prostate cancer may choose to supplement their conventional treatment with one or more forms of complementary or alternative medicine (CAM).…”
Section: Introductionmentioning
confidence: 99%
“…28 Cohort studies consistently reported an increased risk of erectile dysfunction associated with radical prostatectomy (RR 1.6, 95% CI 1.3-1.8, affecting 23.4% or 234 per 1000 of men) compared with no treatment. [39][40][41][42][43] Both RCTs 28,38 and cohort studies [39][40][41][42] found that radical prostatectomy increased the risk of urinary incontinence compared with watchful waiting (metaanalysis of trial data: RR 3.2, 95% CI 2.3-4.6; 17.8% of men or 178 per 1000 affected 13 ). In addition, between 11% and 21% of men will experience short-term (< 30 d) postoperative complications, such as infection, additional surgery and blood transfusions.…”
Section: Benefits and Harms Of Treatmentmentioning
confidence: 99%
“…28,[44][45][46] Trial data indicate that radiation therapy increases the risk of urinary incontinence 47 (not supported by observational studies 13 ) and erectile dysfunction. [39][40][41][42] Combined radiation and hormonal therapy also increases the risk of bowel and erectile dysfunction. 13 Hormonal therapy (androgen deprivation therapy) has been shown to increase the risk of erectile dysfunction (76% v. 33% in control group), but not urinary incontinence (9% v. 6% in control group).…”
Section: Benefits and Harms Of Treatmentmentioning
confidence: 99%